2018
DOI: 10.3390/ijerph15071442
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Wnt and Hh Signaling Pathways in the Pathology of Basal Cell Carcinoma

Abstract: Basal cell carcinoma (BCC) is the most frequently occurring form of all cancers. The cost of care for BCC is one of the highest for all cancers in the Medicare population in the United States. Activation of Hedgehog (Hh) signaling pathway appears to be a key driver of BCC development. Studies involving mouse models have provided evidence that activation of the glioma-associated oncogene (GLI) family of transcription factors is a key step in the initiation of the tumorigenic program leading to BCC. Activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 117 publications
(153 reference statements)
0
31
0
3
Order By: Relevance
“…Based on the relevant literatures regarding the functional interaction between Wnt and Hh pathways in various cancer models, the interaction between these two pathways could be either positive or negative [25]. In few cancer models Wnt is upstream of Hh [10] and in other cancers Hh is upstream of Wnt [26]. Additionally, in an in vitro study with gastrointestinal and lung cancer cells the activation of Wnt signalling pathway has been found to be associated with enhanced expression and activity of Hh signalling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the relevant literatures regarding the functional interaction between Wnt and Hh pathways in various cancer models, the interaction between these two pathways could be either positive or negative [25]. In few cancer models Wnt is upstream of Hh [10] and in other cancers Hh is upstream of Wnt [26]. Additionally, in an in vitro study with gastrointestinal and lung cancer cells the activation of Wnt signalling pathway has been found to be associated with enhanced expression and activity of Hh signalling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were plated in 6 well plates and cultured in DMEM (GIBCO, Invitrogen) media, supplemented with penicillin (100 U/ml), streptomycin (100U/ml) and 10% fetal bovine serum at 37°C in 5% CO 2-95% air atmosphere in a humidi- [12,13]. Development of resistance to a particular drug during the trial period is also an additional drawback as observed in case of Basal Cell Carcinoma [10]. Given the fact it is always necessary to investigate other potential druggable targets and better effective inhibitors of already known aberrant signalling pathways in HCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of functional PTCH, smoothened may be constitutively active, independent of hedgehog control, and may induce overexpression of several target genes including Wnts, CyclinD1 and D2, N-myc, Snail, the anti-apoptotic factor Bcl2 as well as feedback genes of Hh signaling (PATCH1 and 2, Gli1 and huntingtin interacting protein-1, Hip1) [70,71]. The Hh signaling pathway is in conjunction with other important pathways, such as epidermal growth factors (EGF/EGFR), transforming growth factor-β (TGF-β), and Wnt/β-catenin signaling [72,73]. Gli1 is also implicated in replicative immortality achieved by human telomerase reverse transcription transcriptase (hTERT) protein expression regulation [74].…”
Section: Hedgehog Signalingmentioning
confidence: 99%
“…Shh-associated secretory protein binds and inactivates patched1 (PTCH1), resulting in the release of smoothened protein and activation of GLI1, GLI2, and GLI3 receptors. GLI1 predominantly functions as a transcription activator, while GLI2 and GLI3 function as either an activator or repressor 21 . GLI1 activation initiates the expression of downstream target genes involved in proliferation (cyclin D1), survival (B-cell lymphoma-2, Bcl2), metastasis (Snail), and stem cell activation (Nanog and SOX2) 22 .…”
Section: Introductionmentioning
confidence: 99%